TB-03 Newly Established Meningioma Organoid Model Elucidated an Important Role of FOXM1 in Meningioma Progression. (28th November 2020) - Yamazaki, Shintaro; Ohka, Fumiharu; Hirano, Masaki; Motomura, Kazuya; Tanahashi, Kuniaki; Takeuchi, Kazuhito; Shiraki, Yukihiro; Aoki, Kosuke; Kitano, Yotaro; Shimizu, Hiroyuki; Yamaguchi, Junya; Maeda, Sachi; et al.
Abstract: Meningioma is the most frequently occurring intracranial neoplasms in adults. Tumor removal surgery and radiotherapy were the widely accepted standard treatment for meningioma. Most meningioma cases were cured by extended total removal. However, some tumors develop in locations less amenable to resection, resulting in tumor recurrence after incomplete tumor removal followed by radiotherapy. Although several comprehensive studies have revealed frequently found molecular alterations of meningiomas, effective treatment reagents targeting specific molecular alterations have not been identified yet because of limited number of representative research models such as tumor cell lines or animal models of meningiomas. Recently developed 3D culture technologies have led to the development of novel cancer models, termed organoid models, due to their quite high efficiency of establishment. In this study, we established primary organoid culture methods using malignant meningioma cell lines (e.g. HKBMM and IOMM-Lee) and patient-derived meningioma tissues. Using this novel method, we have been able to establish six organoid models (four WHO grade I meningiomas, one WHO grade III one and one solitary fibrous tumor (SFT)) using tumor tissues derived from six consecutive patients with 100% success rate. Histological analyses, whole exome sequencing and copy number analyses revealed that these organoids exhibited consistent histological features and molecular profiling with those of parental tumors. Using public database, we identified upregulated FOXM1 was correlated with increased tumor proliferation. Over-expression of FOXM1 in benign meningioma organoids increased organoid proliferation, while depletion of FOXM1 in malignant ones decreased their proliferation. We revealed that novel organoid model for meningioma enable to shed light on the tumor biology of meningioma.